A study of internal parasites in free range turkeys in Simpang Renggam Farm, Johor, Malaysia - Prasad, Ashnita Shivani; Idris, Lokman Hakim (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Free range rearing is an integral part of turkey farming in most of the developing countries of world. Turkeys raised in free-range system are free to live and browse outside. Very scarce reports regarding internal parasites on free ranging turkeys are available from Malaysia. The present research project was designed to study internal parasites in free range turkeys in Malaysia from Simpang Renggam Farm, Kluang District, and Johor. The blood parasites found in turkeys were Leucocytozoon spp and Plasmodium spp at 1 (20%) and 2 (40%). Three species of fecal oocyst/egg infected the turkeys. Eimeria spp had the highest prevalence of 3(60%) followed by Heterakis gallinarum 2(40%) and Capillaria sp 1(20%). For the gastrointestinal worms, Capillaria spp worm were found at 20% and Acanthocephalan worm was found at 2(40%). Generally, of these 5 female birds, 2 (40%) were infected with blood parasites and 4(80%) were infected with gastrointestinal parasites. The study is second in its nature in providing the valuable information regarding endoparasites in turkeys from Malaysia. This information will essentially be helpful for the researchers and local veterinarians to develop strategies for both treatment and control of these endoparasites affecting turkeys.